ESL students’ attitude, learning problems, and needs for online writing - Noriah Ismail,; Supyan Hussin,; Saadiyah Darus, (Penerbit UKM, 2012)
In many instances, negative attitudes towards writing as well as other language learning problems have been linked to ESL students’ poor performance in writing. The study investigates ESL tertiary students’ writing attitude and the learning problems they face in BEL 311 writing course at MARA University of Technology. The participants in the study were 60 Part Three Diploma students taking BEL 311 course, and 4 writing instructors who have been teaching this course for more than 5 years. The students were given a set of needs analysis questionnaires, and the lecturers were interviewed. In addition, both groups of participants were asked to describe the important elements which they perceive as useful for a supplementary online writing program. The results indicate that the lecturers felt the majority of the students have negative attitude towards writing as they would procrastinate. They are also careless and dislike writing. The findings from the participants also revealed that they perceive writing in English as difficult and they dislike it. In addition, both groups of participants also perceive that the students’ learning problems, which affect their writing quality, include the lack of practice time being allocated in class, dull writing activities and the lack of emphasis towards critical thinking in their writing course. Furthermore, they suggested that a special online writing program which can act as a supplement for the course and help to enhance the learners’ writing ability and interest.